Transformations in world order of food: what the war between Russia and Ukraine changed for Egypt as a first wheat importer - Kongolo, Marie Mavunda (2025)
Wheat serves as a staple food in numerous countries, making its production and supply crucial for global food security. The (re)emergence of significant producers and exporters such as Russia, Ukraine, and Romania, has notably transformed the global food landscape. Nations faced with food insecurity, like Egypt (the world's largest wheat importer) are particularly affected by these shifts. Historically, the global food order has undergone various transformations. However, the current trend, especially since Russia's invasion of Ukraine in 2022, is characterized by the geoeconomics of wheat and its strategic use as an instrument of war. According to the World Food Program, only seven countries account for 86% of global wheat exports, with three countries holding 68% of the world's wheat reserves. This concentration grants these nations substantial power in the global wheat market.